Revolutionizing the energy sector: exploring diversified blockchain platforms for a sustainable future - Jayavarma, Athira; Parakkat Kesava Panikker, Preetha; Nair, Manjula G. (Frontiers in Blockchain, 2025)
Blockchain technology has caused a significant transformation in the global energy sector as it is increasingly applied in producing, distributing, trading, and managing energy. The incorporation of blockchain in the industry presents unprecedented opportunities for creating secure and decentralized systems of trading energy systems that are not only secure and resilient but also transparent. The paper explores a detailed analysis of various blockchain platforms and endeavors to collapse the existing gaps in the advanced research of blockchain systems supporting the development of energy trading applications. Precisely, this paper gives in-depth details of some of the popular blockchain platforms, and it primarily focuses on the platforms’ security, scalability solutions, consensus methods, strategies for mitigating cyberattacks, privacy-preserving mechanisms, regulatory considerations, the integration of artificial intelligence for platform optimization and suitability in energy trading based on the existing information. It helps energy providers select the best blockchain platform for their energy trading projects. The detailed examination aims to further improve energy trading efficiency, reliability, and sustainability via the most suitable blockchain platform.